Higher education student responses to the use of online assessments on biology material - Yuni Pantiwati; Tasya Novian Indah Sari; Riantina Fitra Aldya; As'ad Syamsul Arifin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The integration of technology into learning assessment activities makes it easy for educators to carry out online assessments which provide convenience for students and an effective assessment. The purpose of this research is to find out the response of students in the Biology Education Study Program towards online assessment platforms for Biology materials and learning. This typed of researched was quantitative descriptive used a surveyed method which had been carried out in the odd semester of 2021/2022 with the researched subjects being active students of Biology Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Malang, a total of 114 students.  The data collection technique used a surveyed method used Google Form and the data was analyzed descriptively. The results of the studied showed that of the 5 assessment platforms used in the researched, Quizizz and Google Form platforms was the preferred assessment platforms by students   The results of this study indicate that in the future we need a product that can meet the needs of the assessment and according to the needs of the respondents. This product corresponds to the advantages and disadvantages of each online assessment platform. Thus, creating a more effective and efficient online assessment platform.